Food for Thought: The Translation of Culinary References in Animation - González-Vera, Pilar (Íkala, Revista de Lenguaje y Cultura, 2015)
Food has traditionally been a cultural symbol reflecting historical roots in every country. It is precisely those cultural bonds that have made the translation of culinary references so difficult. The translation of food-related terms requires translators to consider, on the one hand, the cultural associations embedded in these terms, their meaning and function in the ST and, on the other hand, the translatability of the terms in the TT. As a socio-cultural phenomenon, food plays a fundamental role in the process of globalization in which we are immersed. We cannot disregard the fact that cultures are merging and that the introduction of new food terminology in our lexicon provides irrefutable evidence of globalization and acculturation. This paper focuses on the analysis of the role of food and its translation in theprocess of globalization. It analyses the relationship between food and culture in animated films like the Shrek saga, The princess and the frog, or Brave —films where food is not the focal point, but where it serves different purposes, such as acculturation, recreation of cultural identities and stereotypes, or humour. The analysis includes a study of the translation techniques applied in the dubbed versions of these films and their relationship to the process of domestication and foreignization in order to assess the social implications in texts aimed at a young audience.